Petty Corruption and Citizen Feedback - Charles Angelucci; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2015)
Numerous countries are introducing citizen feedback schemes to tame corruption. We study how best to incorporate feedback in public officials' incentives. The main novelty of our proposal is to allow citizens to directly influence officials' pay. We consider a situation in which entrepreneurs must comply with regulation before undertaking a risky activity. Officials verify compliance to determine whether to grant permits, and may engage in either bribery or extortion. Without feedback, the government has no choice but to tolerate bribery, which leads to too many permits being granted and large negative externalities. By contrast, implementing a feedback scheme that (i) rewards entrepreneurs filing complaints and (ii) ties officials' pay to these complaints makes deterring both bribery and extortion possible. Our proposed scheme does not require the government to be able to verify the accuracy of complaints. In an extension, we incorporate the role played by intermediaries, and show their involvement makes the feedback scheme even more valuable.
Keywords: H11; H83; O17; D73; 330; corruption; extortion; bribery; citizen feedback; bureaucracy intermediaries